Lateral Habenula determines long-term storage of aversive memories - Tomaiuolo, Micol; Gonzalez, Carolina; Medina, Jorge H.; Piriz, Joaquin (Frontiers in Behavioral Neuroscience, 2014)
The Lateral Habenula (LHb) is a small brain structure that codifies negative motivational value and has been related to major depression. It has been shown recently that LHb activation is sufficient to induce aversive associative learning; however the key question about whether LHb activation is required for an aversive memory to be formed has not been addressed. In this article we studied the function of the LHb in memory formation using the Inhibitory Avoidance task (IA). We found that LHb inactivation during IA training does not disrupt memory when assessed 24 hours after, but abolishes it 7 days later, indicating that LHb activity during memory acquisition is not necessary for memory formation, but regulates its temporal stability. These effects suggest that LHb inactivation modifies subjective perception of the training experience.